Karl Bankl. An Austrian at the Head of the So-called Church Department of the Olomouc Gestapo - Vajskebr, Jan; Zumr, Jan (Historica Olomucensia, 2021)
Karel Bankl was, in many respects, a typical Austrian member of low-level Gestapo management. Having fought in the First World War, he found a job with the Viennese police after the disintegration of Austria-Hungary. Although he served in the state administration, he actively supported the Nazi party. After Austria was annexed in March 1938, Bankl was transferred to the Vienna Gestapo headquarters. He was responsible for the Catholic Church affairs at the Department of Churches, Sects, and Jews, before being deployed in the occupation of Moravia on 15 March 1939. He spent the rest of his police career and of his life in the Protectorate of Bohemia and Moravia. He was stationed the longest in Olomouc, actively persecuting the Jewish population, at whose expense he was quick to enrich himself. He was then transferred to the Prague headquarters, from where he first went to Ceske Budejovice and then to Kladno. Although his career was complicated by a number of circumstances, such as old age, poor health, a wrong "racial profile", insufficient education, and the absence of offspring, he was viewed by his superiors as an efficient and politically reliable official. Although the details of Bankl's last days are not known, it is likely that he was killed or committed suicide at the end of World War II.
Keywords: Protectorate of Bohemia and Moravia; Austria; World War II; the Gestapo; the Holocaust